AWS Certified SysOps Administrator (associate) : complete video course - Smith, Chad (LiveLessons (Indianapolis, Ind.), 2018)
The AWS Certified SysOps Administrator (Associate) Complete Video Course provides directed study for the updated certification exam, which includes covering exam logistics, the seven question domains, and provides sample exam questions. The AWS Certified SysOps Administrator (Associate) Complete Video Course provides nearly seven hours of directed study for the September 2018 updated certification exam. Chad Smith, AWS and Linux instructor and author, will walk you through each objective on the exam as well as real-world situations to help you learn the concepts necessary to pass the exam and become an AWS Certified SysOps Administrator. The course starts with an overview of the certification exam, and the prerequisites and skills required to be a successful candidate for certification. Chad then jumps into the seven exam domains: Monitoring and Reporting; High Availability; Deployment and Provisioning; Storage and Data Management; Security and Compliance; Networking; and Automation and Optimization. Throughout each lesson, Chad will provide explanations and real-world scenarios. Each lesson ends with examples of the questions you will encounter on the exam. Chad will walk through the questions, identify key terms, and explain the process to determine the correct answer.